2018
DOI: 10.1016/j.healun.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Donor predicted heart mass as predictor of primary graft dysfunction

Abstract: Undersized donor hearts by ≥30% by PHM may increase rates of PGD after transplantation, confirming that PHM provides more clinically appropriate size matching than TBW. Better size matching may ultimately allow for expanding the donor pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…In support of this, donor-recipient PHM undersizing was associated with primary graft dysfunction in a recent study, whereas weight was not. 13 Our study supports this finding, because we observed that recipients severely undersized for PHM experienced increased mortality early after HTX.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In support of this, donor-recipient PHM undersizing was associated with primary graft dysfunction in a recent study, whereas weight was not. 13 Our study supports this finding, because we observed that recipients severely undersized for PHM experienced increased mortality early after HTX.…”
Section: Discussionsupporting
confidence: 87%
“…11,12 Recently, PHM, but not body weight, predicted the development of primary graft dysfunction after HTX. 13 Given uncertainty regarding the optimal metric of donor-recipient size match, we compared the ability of PHM to 4 other size match metrics-weight, height, BMI, and body surface area (BSA)-to predict 1-year mortality after HTX. We also identified the effect of donor-recipient size match on donor heart turn down for size during allocation.…”
mentioning
confidence: 99%
“…The lack of association suggests that different inflammatory and immune pathways lead to PGD and ACR after lung and heart transplantation. The incidence of PGD in this study is similar to previous reports . According to the ISHLT Registry, 27.3% of lung transplant recipients were treated for at least 1 episode of ACR in the 1st year post‐transplant .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the ISHLT developed a definition for PGD after lung transplantation in 2005 and subsequently refined the criteria in 2016 . The standardization of PGD definitions has provided a more consistent approach for scoring PGD and created a platform to evaluate potential risk factors . The pathogenesis of PGD represents both inflammatory and ischemia‐reperfusion–related mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…After the recent introduction of the ISHLT consensus conference definition of PGF, contemporary data suggest an overall incidence of 10% to 36%, with severe PGF—likely the most clinically relevant entity—occurring in 8% to 18% of HT recipients (Table ) . Similar to difficulties in reporting the incidence of PGF due to non‐universal definitions, reported risk factors have also varied substantially by era, transplant center, and patient population.…”
Section: Preoperative Risksmentioning
confidence: 99%